2019
DOI: 10.1002/met.1804
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of growth functions that can increase irrigated wheat yield under climate change

Abstract: This study assessed the growth of wheat under climate change conditions (increases in CO2 and temperature) in southwestern Iran. Future climate data were projected using long‐term climate data for radiation and minimum and maximum temperatures for the baseline period 1980–2010. The future climate scenarios made use of delta changes from the Coupled Model Intercomparison Project Phase 5 (CMIP5) in the R package of the Agricultural Model Intercomparison and Improvement Project for 2040–2070. After generating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The ability of APSIM-Wheat model to predict yield in the semi-arid environment was confirmed by previous studies 91 – 95 . Application of APSIM-Wheat for grain yield simulation showed reasonable predictive results not only in semi-arid climate 43 , 46 , 96 99 , but also in arid 44 , 45 , 100 and Mediterranean 41 , 42 , 101 103 environments.…”
Section: Discussionmentioning
confidence: 89%
“…The ability of APSIM-Wheat model to predict yield in the semi-arid environment was confirmed by previous studies 91 – 95 . Application of APSIM-Wheat for grain yield simulation showed reasonable predictive results not only in semi-arid climate 43 , 46 , 96 99 , but also in arid 44 , 45 , 100 and Mediterranean 41 , 42 , 101 103 environments.…”
Section: Discussionmentioning
confidence: 89%
“…Our findings also converge with studies carried out in southwestern Iran, that suggested a shortening of the wheat-growing season length of 7.5 and 9.3% under RCP4.5 and RCP8.5, respectively, for 2040-2070 with respect to the baseline, 1980-2010. [36]. Reference [37] reported that temperatures during the growth period for winter wheat under climate change would increase significantly compared to baseline, while the length of the growing season would decrease.…”
Section: Length Of Crop Season Under Climate Changementioning
confidence: 99%
“…Atmosphere 2020, 11, x FOR PEER REVIEW 15 of 25 respectively, for 2040-2070 with respect to the baseline, 1980-2010. [36]. Reference [37] reported that temperatures during the growth period for winter wheat under climate change would increase significantly compared to baseline, while the length of the growing season would decrease.…”
Section: Length Of Crop Season Under Climate Changementioning
confidence: 99%
“…The wheat crop area worldwide is more than 220 million ha, with 5.7 million ha in Iran. Studies show that changes in climatic factors such as temperature will affect wheat yield (Eyni-Nargeseh et al, 2020). The agricultural sector in Iran produces about 18% of the GDP, 25% of non-oil exports, 20% of employment, and 85% of the total food supply, therefore it plays a very significant role in economic growth.…”
Section: Introductionmentioning
confidence: 99%